Management of paediatric humeral shaft fractures and associated nerve palsy - O’Shaughnessy, M. A. (J Child Orthop, 2019)
PURPOSE: The aim of this study is to review the management of all paediatric humerus diaphyseal fractures treated at a single institution over a 20-year period. METHODS: Retrospective review from between 1996 and 2016 identified 96 humerus shaft fractures in paediatric patients (0 to 17 years). After excluding those deceased from inciting trauma, pathological and perinatal fractures, 80 patients remained for analysis. Data collected included age, fracture type, displacement, nerve palsy, treatment, complications and time to union. Radiographs were reviewed at the time of injury and at latest follow-up. RESULTS: Of 80 paediatric humeral diaphyseal fractures, 65 (81%) were treated with immobilization. In all, 15 (19%) fractures were treated with surgical stabilization. Most common indications were fracture displacement, open fractures and to improve mobilization in patients with multiple injuries. Fractures were stabilized with a plate (eight), flexible nails (five), external fixation (one) and percutaneous pinning (one). The operative group, compared with the nonoperative group, was older, had more high-energy mechanisms, more open fractures and increased fracture displacement. All patients in the nonoperative and operative groups went on to union with minimal complications. A nerve palsy was present in five patients (6%)with three of the five involving the radial nerve (4%). All nerve palsies were observed and had full neurological recovery. CONCLUSION: Over a 20-year period nonoperative management of paediatric humerus shaft fractures was successful in the majority of patients. Operative stabilization, when rarely indicated, had a low complication rate and improved radiographic alignment. All nerve injuries fully recovered without surgical intervention. LEVEL OF EVIDENCE: IV